Preparing Rural Preservice Teachers for Diversity - Kerri J. Wenger; Jan Dinsmore (Journal of Research in Rural Education, 2005)
This 2-year evaluative self-study of a cohort teacher preparation program in rural eastern Oregon explored preservice teachers' perceptions of their preparedness to teach diverse students. Using qualitative methods, teacher educators examined preservice teachers' assumptions about student diversity in rural schools where they planned to teach. Characteristics of experiences that preservice teachers found helpful and unhelpful in their preparation to teach linguistically and culturally diverse students are described. Data suggested that the cohort model used for teacher preparation program delivery was important in supporting inquiry that sensitized rural preservice teachers to diverse learners' funds of knowledge.